The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/016235320903300205
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Paternal Influence on High-Achieving Gifted Males

Abstract: is professor of educational psychology in the College of Education at the University of Georgia in Athens where he teaches graduate courses in gifted education and qualitative research methods. Alexander R. Pagnani is a doctoral student in educational psychology-gifted and creative education at the University of Georgia in Athens. Daniel R. Hammond earned his master's degree in educational psychology-gifted and creative education at the University of Georgia. He is a doctoral student in counseling psychology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…This finding further supports the view that student's interest and personal choice far supersedes the influence of relations or close friends, tutors, family members or celebrities as opposed to Stafford (1994). Our finding also appears to be inconsistent with some past studies on career choice decisions that have shown that parental influence and tutors have significant influence on student choice of careers (Hebert &Pagnani, 2009;Bradford, Buck, & Myers, 2001). …”
Section: Personalities and Choice Of Marketing Majorcontrasting
confidence: 99%
“…This finding further supports the view that student's interest and personal choice far supersedes the influence of relations or close friends, tutors, family members or celebrities as opposed to Stafford (1994). Our finding also appears to be inconsistent with some past studies on career choice decisions that have shown that parental influence and tutors have significant influence on student choice of careers (Hebert &Pagnani, 2009;Bradford, Buck, & Myers, 2001). …”
Section: Personalities and Choice Of Marketing Majorcontrasting
confidence: 99%
“…Finally, black fathers engage in positive racial socializing practices, sending their children messages of racial pride, preparing them to navigate potential racial barriers, and emphasizing racial resiliency and self-determination (Mandara 2006;Greif, Hrabowski, and Maton 1998). These types of paternal involvement practices are associated with increased academic and professional achievement, decreased delinquency, and overall well-being of black children (Caldwell et al 2004;Dubowitz et al 2001;Hebert, Pagnani, and Hammond 2009).…”
Section: Masculinity Manhood and Black Fathersmentioning
confidence: 99%
“…White and Asian American parents were the most likely to identify self-satisfaction in their definitions of academic success, whereas fathers of all ethnicities were more likely than mothers to emphasize external definitions of success such as high grades or entry to a successful college or career path (Ablard, 1996(Ablard, /1997. Fathers of high-achieving gifted males were also found to hold high standards for their sons and to share in their son's sense of accomplishment (Hébert, Pagnani, & Hammond, 2009). …”
Section: Theme 1: Studies Of Parent Influencementioning
confidence: 99%